Calculation Program Design of the Involute Spline Geometric Parameter - Geng Xichun; Wang Fugang; Wu Yuzhen (Jixie chuandong)
The calculation methods of all the geometric parameters and their tolerance involved in the latest national standard（ GB/T 3478. 1-2008 GB/T 3478. 9-2008） of the involute spline are summarized and sorted,the process of program calculation is determined respectively,the successful operation of the program is realized through the programming of VB program code. Finally,the accuracy of the calculation result is proved by the comparison with the national standard given numerical value,which also proves the practicality of the calculation procedure.